Examination of mechanical properties of graphene allotropes by means of computer simulation - Mrozek, Adam; Burczyński, Tadeusz (Computer Assisted Methods in Engineering and Science, 2013)
The effective mechanical properties and the stress-strain relations of the eight types of the graphene allotropes are presented in this paper. Series of the tensile and shear tests are performed using the non-equilibrium molecular dynamics (NEMD) and the adaptive intermolecular reactive bond order (AIREBO) potential. The methodology of the investigation as well as obtained results are explained and discussed in detail. Where possible, the achieved results are compared with the data available in the scientific literature in order to validate our molecular dynamics models and simulations. In other cases, i.e., where only information about structural or electronic properties is available, presented results can complement the knowledge about these particular planar carbon networks.